Evaluation of hemicell® on growth performance of late nursery pigs - Lenehan, N.A.; Groesbeck, C.N.; Hastad, C.W.; Keegan, T.P.; Lawrence, K.R.; Young, M.G.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 276 pigs (initially 21.9 lb) was used to determine the effects of added Hemicell® on growth performance. Hemicell® is a patented fermentation product of Bacillus lentus. The active ingredient in the fermentation product is β-mannanase. However, other enzymes such as amylase, xylanase, cellulases, and α-galactosidase also are present. It is claimed that Hemicell® degrades β-mannan in feed, thus, removing its effects as an antinutritive factor in swine diets. Dietary treatments were arranged as a 2 x 3 factorial, with or without 0.05% Hemicell®, in diets with 3 levels of energy density (1,388, 1,488, 1,588 ME, kcal/lb). The 100 kcal increments were achieved by the addition of wheat bran or soy oil to a corn-soybean meal based diet. The addition of Hemicell® to the diets, regardless of energy level, did not lead to an improvement in growth performance in these late nursery pigs. Increasing energy density of the diet, however, resulted in an improved ADG and F/G.
Keywords: Weanling pigs; Hemicell®; Enzyme; Swine